Musical colossal drama project-based learning to boost students’ engagement in English language learning - Upik Hastuti (Erudita: Journal of English Language Teaching, 2022)
Various factors influence students to be active in learning English. One of them is role-playing and drama in learning songs. The present study aims to showcase EFL students’ emotions in learning English as a foreign language by adopting musical colossal drama project-based learning Nested in a qualitative case study, the eleventh-grade students of a senior secondary school in Purbalingga, Central Java, Indonesia were recruited to participate. Data were garnered through semi-structured interviews and classroom observation. The data were analyzed by employing data reduction, data display, and conclusion verification. Findings of the study demonstrate that the senior high school EFL students showed positive emotions when they engaged in learning English, particularly adopting songs, in the frame of musical colossal drama project-based learning. Another finding reveals that musical colossal drama project-based learning boosted the EFL students’ 21st century skills, i.e., critical thinking, creative thinking, communicating, and collaborating. This study promotes some empirical evidence for how musical colossal drama is organized to foster students’ involvement in a project-based English language learning.